2019
DOI: 10.30715/doxa.v21i1.12931
|View full text |Cite
|
Sign up to set email alerts
|

Fetichismo virtual na vida de um hikikomori brasileiro: um estudo de caso

Abstract: RESUMO: O fenômeno hikikomori, identificado no Japão nos anos de 1990, é uma condição psicossocial em que a pessoa, deliberadamente, se isola da sociedade por seis meses ou mais. Trata-se de um problema crescente no mundo. O caso descrito nesse estudo refere-se a um homem de 38 anos que havia abandonado o emprego há mais de dez anos e se mantido em isolamento social por mais de cinco. Sua rotina consistia em acessar jogos e páginas pornográficas na internet. A análise deste caso destacou alguns fatores psicodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…4,10 The prevalence of hikikomori in Brazil is unknown due to a lack of empirical research on the phenomenon; however, the syndrome has been reported three times in Brazilian patients. 9,12,13 Recently, our group described the complete treatment program for one of these cases. The patient reported substantial clinical improvement after a multimodal intervention strategy, including pharmacological treatment of comorbidities, family psychoeducation, and the use of different psychotherapy techniques.…”
mentioning
confidence: 99%
“…4,10 The prevalence of hikikomori in Brazil is unknown due to a lack of empirical research on the phenomenon; however, the syndrome has been reported three times in Brazilian patients. 9,12,13 Recently, our group described the complete treatment program for one of these cases. The patient reported substantial clinical improvement after a multimodal intervention strategy, including pharmacological treatment of comorbidities, family psychoeducation, and the use of different psychotherapy techniques.…”
mentioning
confidence: 99%
“…This is the third case of hikikomori described in Brazil, with the first reporting spontaneous recovery after 29 years of social withdrawal, 7 and the second presenting partial clinical improvement after 9 months of weekly psychoanalytical psychotherapy. 8 Nevertheless, this is the first Brazilian case of recurrent hikikomori, and the first in which a multimodal treatment approach was applied.…”
mentioning
confidence: 91%
“…Participants from all the studied countries perceived hikikomori as a present syndrome in their own countries, and most of them considered the hikikomori phenomenon to be associated with rapid socio-cultural changes derived from globalization. Other reports include cases in countries such as China ( Wong et al, 2017 ), Spain ( Ovejero et al, 2014 ), and Brazil ( Gondim et al, 2017 ; Prioste and Siqueira, 2019 ). As such, the growing prevalence of such tendencies across the world requires additional investigation, especially in countries outside of Japan.…”
Section: Introductionmentioning
confidence: 99%
“… Gondim et al (2017) described the case of a 25-year-old man, without previous history of psychiatric treatment; after breaking up with his girlfriend and quitting his job, the man stayed in his parents’ house for 29 years, having minimal contact with other people and rarely going outside. Prioste and Siqueira (2019) described the case of a 38-year-old man who had quit his job more than 10 years prior and refrained from social relationships for more than 5 years, spending his time playing computer games and browsing the internet. These cases showed some overlapping tendencies with cases in Japan.…”
Section: Introductionmentioning
confidence: 99%